Guillain-Barre Syndrome Deterioration After an Abdominal Surgery; A Case Report - Khayatzadeh, Simin; Khosroshahi, Nahideh; Habibi Zoham, Mojdeh (Iranian Journal of Child Neurology, 2022)
Guillain-Barre syndrome is an acute ascending paralysis accompanied with autonomic symptoms like abdominal pain. Here we present a 13-year-old boy with lower extremities pain and sensory disturbances with presumptive diagnosis of Guillain-Barre syndrome who experienced severe progression of disease after receiving general anesthesia due to an appendectomy. Whether the progression was due to the natural history of GBS, immunosuppression induced by surgical stress, or usage of anesthetic medications remained unclear.